Glutaminase and MMP-9 Downregulation in Cortex and Hippocampus of LPA1 Receptor Null Mice Correlate with Altered Dendritic Spine Plasticity - Peñalver, Ana; Campos-Sandoval, José A.; Blanco, Eduardo; Cardona, Carolina; Castilla, Laura; Martín-Rufián, Mercedes; Estivill-Torrús, Guillermo; Sánchez-Varo, Raquel; Alonso, Francisco J.; Pérez-Hernández, Mercedes; Colado, María I.; Gutiérrez, Antonia; et al. (Frontiers in Molecular Neuroscience, 2017)
Lysophosphatidic acid (LPA) is an extracellular lipid mediator that regulates nervous system development and functions acting through G protein-coupled receptors. Here we explore the crosstalk between LPA1 receptor and glutamatergic transmission by examining expression of glutaminase isoforms in different brain areas isolated from wild-type and KOLPA1 mice. Silencing of LPA1 receptor induced a severe down-regulation of KGA (GLS) protein expression in several brain regions, particularly in brain cortex and hippocampus. Immunohistochemical assessment of protein levels for the second type of glutaminase isoform, GLS2, did not detect substantial differences with regard to wild-type animals. The regional mRNA levels of GLS were determined by real time RT-PCR and did not show significant variations, except for prefrontal and motor cortex values which clearly diminished in KO mice. Total glutaminase activity was also significantly reduced in prefrontal and motor cortex, but remained essentially unchanged in the hippocampus and rest of brain regions examined, suggesting activation of genetic compensatory mechanisms and/or posttranslational modifications to compensate for KGA protein deficit. Remarkably, Golgi staining of hippocampal regions showed an altered morphology of glutamatergic pyramidal cells dendritic spines towards a less mature filopodia-like phenotype, as compared with wild-type littermates. This structural change correlated with a strong decrease of active matrix-metalloproteinase 9 in cerebral cortex and hippocampus of KOLPA1 mice. Taken together, these results demonstrate that LPA signaling through LPA1 influence expression of the main isoenzyme of glutamate biosynthesis with strong repercussions on dendritic spines maturation, which may partially explain the cognitive and learning defects previously reported for this colony of KOLPA1 mice.